Organic and inorganic solutes in Salicornia neei Lag. under blades of irrigation and fertilization in Ceara semiarid, Brazil - Alves, Paulo Ricardo; Lucena, Eliseu Marlônio Pereira de; Bonilla, Oriel Herrera; Marques, Elton Camelo; Gomes-Filho, Enéas; Costa, Cesar Serra Bonifácio (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
The halophyte Salicornia neei Lag. can be used as a phytoremediation agent in salt degraded areas. The objective of this work was to evaluate the organic (carbohydrate and N-aminosoluble) and inorganic (Na+, K+ and Cl-) solutes contents in S. neei submitted to different blades of irrigation and fertilization in Ceara semiarid. The samples were obtained in culture carried out in Ocara-CE. Four areas of 100 m2 were prepared with different treatments (denominated T1, T2, T3, T4) of irrigation: once a day (0.15 m3 / day) in T1 and T2, and two irrigations a day (0.30 m3 / day) in T3 and T4, for 30 minutes each, and fertilization only in treatments T2 and T4 with NPK (10:28:20). Two samples were collected per treatment at 60, 90 and 120 days after planting (DAP). The total soluble carbohydrate content of the fertilized plants did not differ between the days of collection. The largest concentrations of N-aminossoluveis occurred to 120 DAP in plants with one irrigation and without fertilizer. Plants with one irrigation and without fertilizer had the greatest levels of Na+ and K+. The Cl- levels did not differ between the dates in the collection with two plants irrigation. It is concluded that the highest levels of organic and inorganic solutes occurred in the treatments with and without irrigation.